1991
DOI: 10.1007/bf00185011
|View full text |Cite
|
Sign up to set email alerts
|

Application of light emitting diodes as a light source to a photosynthetic culture of Chlorobium thiosulfatophilum

Abstract: Economical light energy supply plays a Key role in determining the success of industrial application of photosynthetic microorganisms.The bacteriochlorophyll a of C. thiosulfatophilum harvests the light at 760 nm, which oxidizes toxic HzS by photosynthesis. Light emitting diode(LED), which emits a maximum intensity at 710 nm and 60% of its maximum at 760 nm, was adopted as an alternative light source to inefficient incandescent light. With the array of the LEDs adjustable to the reactor wall 95% of -the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…LEDs have many advantages over other light sources, including high irradiance output with low heat dissipation, long lifetime, small size, and a high capacity to control the spectral composition (Lee and Palsson 1995;Morrow 2008;Olsson et al 2007), and they have been widely adopted in Values are the means ± SD (n=6) Φ PSII effective quantum yield, α the initial slop, rETR max relative electron transport rate at light saturation, E k (μmol photons m −2 s −1 ) irradiance at onset of light saturation cultivation of higher plants and microalgae (Kim et al 1991;Lee and Palsson 1995;Wang et al 2007). In this study, blue light was provided by LEDs, and they were shown to be highly efficient for both gametophyte reproduction and sporeling growth in S. japonica.…”
Section: Discussionmentioning
confidence: 99%
“…LEDs have many advantages over other light sources, including high irradiance output with low heat dissipation, long lifetime, small size, and a high capacity to control the spectral composition (Lee and Palsson 1995;Morrow 2008;Olsson et al 2007), and they have been widely adopted in Values are the means ± SD (n=6) Φ PSII effective quantum yield, α the initial slop, rETR max relative electron transport rate at light saturation, E k (μmol photons m −2 s −1 ) irradiance at onset of light saturation cultivation of higher plants and microalgae (Kim et al 1991;Lee and Palsson 1995;Wang et al 2007). In this study, blue light was provided by LEDs, and they were shown to be highly efficient for both gametophyte reproduction and sporeling growth in S. japonica.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria can be suspended in a liquid phase or immobilized on different carriers. By comparison of the bioconversion of H 2 S to elemental sulfur using Chlorobium thiosulfatophilum cultivated in suspension or immobilized in alginate carrier, it was found that the fixed cells consumed 30% less light energy than the free cells at the removal rate of H 2 S 68 mg/(L h) (Kim and Chang, 1991a).…”
Section: Bioreactors For Desulfurization Using Phototrophic Bacteriamentioning
confidence: 99%